NECESSITY OF CUSTOMER LOYALTY FORMATION AND ITS PECULIARITIES IN THE TELECOMMUNICATION SERVICES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Everyday life is unimaginable without telecommunication services; they are the significant players in the national economy. All business activities, including the ones of telecommunication services, are directed towards the satisfaction of customers’ needs and wants, and hence towards the profit earning. This process, in its turn, entails the formation of different company/customer relations, where both parties want to gain something out of these relations. The company strives, first of all, to increase the turnover and profit, while the customer wants to receive the desired services, information and the proper attitude. These customer gains can be basis of the loyalty formation, that is very important for the company, because the process of attracting new consumers always involves spending money, time and energy. The goal of this work is to explore the loyalty formation process and its peculiarities in the telecommunication services. Based on the results of the study, it was found that the experts rated the offer of corporate loyalty programs at the lowest, then followed the service offer and the price, but slightly higher the service quality. The experts assigned the highest rating to the prestige of the service. Based on the low assessment of the experts in the telecommunication industry of the loyalty program offer, the authors propose the conceptual consumer loyalty model for the practical use.